Early Reproductive Education Through The Utilization of Youtube Videos for Early Childhood Education Student on Anticipating Society 5.0 - Fatmazora Fatmazora; Lili Kasmini; Siti Mayang Sari (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
Early reproductive education is an important preventive effort to instill self-awareness, body understanding, and self-protection skills in early childhood, especially in the Society 5.0 era characterized by the massive use of digital technology. This study aims to describe the implementation of early reproductive education through the utilization of YouTube videos as a learning medium for Early Childhood Education (PAUD) students. The research employed a descriptive qualitative approach involving PAUD teachers, parents, and students as research subjects. Data were collected through observation, interviews, and documentation, while data analysis was conducted through data reduction, data display, and conclusion drawing. The results show that educational YouTube videos, when carefully selected and implemented with guidance from teachers and parents, are effective in introducing basic reproductive concepts, such as body part recognition, gender differences, personal hygiene, and self-protection. The use of this media also increases students’ attention, understanding, and participation, while supporting children’s digital literacy.